2015
DOI: 10.5114/ceji.2015.57146
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of the STAT4 rs7574865 gene polymorphism to the susceptibility to autoimmune thyroiditis in healthy Turk population and psoriatic subgroups

Abstract: IntroductionSTAT4 is an important transcription factor that activates gene transcription as a response to cytokines. Recently, the influence of STAT4 gene on autoimmune disease has been widely studied in many different immune-related diseases. Autoimmune, metabolic and cardiovascular disorders are more common in psoriatic patients. STAT4 may be a unique gene that switches on in autoimmune-related thyroid disease in psoriatic patients.The aim of the study: To explore the association of a STAT4 rs7574865 polymor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 18 publications
1
10
0
1
Order By: Relevance
“…Corresponding results were previously reported in a retrospective analysis of 52 T1D-associated loci, comprising stat4, in over 8,000 T1D cases from the international case-control collection, although only aTPO thyroid antibodies were addressed in that study [38]. Former studies have corroborated the association of stat4 polymorphism with two other major components of the autoimmune polyendocrine syndrome type 2, such as Addison's disease and autoimmune thyroid disease [24][25][26]29]. Observations in small cohorts with polyglandular autoimmunity equally confirm its implication in multiple organ-specific disorders [32,40].…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Corresponding results were previously reported in a retrospective analysis of 52 T1D-associated loci, comprising stat4, in over 8,000 T1D cases from the international case-control collection, although only aTPO thyroid antibodies were addressed in that study [38]. Former studies have corroborated the association of stat4 polymorphism with two other major components of the autoimmune polyendocrine syndrome type 2, such as Addison's disease and autoimmune thyroid disease [24][25][26]29]. Observations in small cohorts with polyglandular autoimmunity equally confirm its implication in multiple organ-specific disorders [32,40].…”
Section: Discussionsupporting
confidence: 76%
“…In line, genetic variants of stat4 are associated with variety of autoimmune disorders, including systemic lupus erythematosus (SLE) [15,18], rheumatoid arthritis [18][19][20], systemic sclerosis [21], and Sjögren syndrome [22]. Organ-specific autoimmune conditions have received much less attention with this regard, although stat4 associations have been reported for celiac disease [23], autoimmune thyroid disease [24,25], and Addison's disease [26]. Most of these associations pointed out rs7574865 as a tagging stat4 single nucleotide polymorphism (SNP) in autoimmunity.…”
Section: Introductionmentioning
confidence: 99%
“…With regard to psoriasis, it has been reported 33 that STAT4 activation results in specific Th1 differentiation, shifting the Th1/Th2 ratio. The number of Th1 cells increased and prolonged responses to IFN-γ, triggering psoriasis [10,23,24] . rs7574865 was one of the most common SNPs in STAT4 and was reported to be associated with the pathogenesis of many autoimmune diseases, e.g., with rheumatoid arthritis in the western Algerian population, juvenile idiopathic arthritis in the Chinese population, early-onset type 1 diabetes, systemic sclerosis, and systemic lupus erythematosus [25][26][27][28][29][30][31] .…”
Section: Discussionmentioning
confidence: 99%
“…Though the evidence between IKZF1 and the risk of psoriasis is limited, several studies have demonstrated its relationship with autoimmune disease systemic lupus erythematosus (SLE) [ 49 ]. IKZF1 has been suggested to affect the STAT4 and IFN pathways [ 50 52 ], both of which involve in the pathogenesis of psoriasis [ 53 55 ] Further studies are worth to validate rs79824801 in an independent sample, to quantify the binding affinity of IKZF1 at this site, and to evaluate the consequence of IFN signaling in the biological mechanism of psoriasis.…”
Section: Discussionmentioning
confidence: 99%